PLACENTAL ALTERATIONS IN SEVERE PREECLAMPSIA AND THEIR MATERNAL AND NEONATAL IMPACTS: INTEGRATIVE LITERATURE REVIEW - Alves, Lívia de Oliveira; Alves, Letícia de Oliveira; Medeiros, Rodolfo de Oliveira; Galhardi, Cristiano Machado; Azevedo, Letícia Francisco de; Ravagnani, Priscila Alvin de Lima; Santos, Ana Lara Gomes dos; Ferreira, Melyssa Xavier; Ferreira, Pamella Xavier; Agulhon, Mariana Gomes; Luiz, Júlia Maria Machado; Ventura, Isabela da Silva; et al. (INTERFERENCE: A JOURNAL OF AUDIO CULTURE, 2025)
Severe preeclampsia remains one of the greatest challenges in obstetrics, with significant impacts on maternal and neonatal morbidity and mortality. This study conducted an Integrative Literature Review with the aim of systematizing evidence on placental alterations associated with the disease and their clinical repercussions. The methodological strategy followed validated steps of Evidence-Based Practice, guided by a structured PICo question (pregnant women with severe preeclampsia; identification of placental alterations; context of maternal and neonatal outcomes). Searches were performed in PubMed, Web of Science, ScienceDirect, and SciELO using DeCS/MeSH descriptors, and included original studies in Portuguese and English. Data were organized into a synthesis matrix, and levels of evidence were classified according to the Joanna Briggs Institute; the selection process was described in accordance with PRISMA. Findings converge toward a pattern of placental impairment characterized by villous infarction, fibrinoid deposition, villous hypoplasia, oxidative stress, and failure in spiral artery remodeling, resulting in uteroplacental hypoperfusion. Clinically, these changes were associated with HELLP syndrome, worsening hypertension, and placental abruption. In neonates, intrauterine growth restriction, prematurity, and perinatal death predominated. Angiogenic biomarkers, particularly PlGF and sFlt-1, have emerged as promising tools for early detection and severity stratification, although they still lack broad multicenter standardization and validation. Recurrent limitations among the studies include methodological heterogeneity, small sample sizes, and the absence of standardized protocols for placental evaluation. It is concluded that the placenta plays a central role in the pathophysiology of severe preeclampsia and in determining clinical outcomes. The adoption of combined biomarker panels, alongside standardized placental analysis protocols and multicenter studies with representative samples, may improve diagnosis, guide early management, and reduce maternal and neonatal morbidity and mortality.